Why are Latin Americans so Unhappy about Reforms? - Ugo Panizza; Mónica Ya\~nez (Inter-American Development Bank, Research Department, 2006)
The objective of this paper is to use opinion polls to document Latin Americans` increasing discontent with reforms and to explore possible explanations for this trend. We test four possible explanations for the rejection of reforms. The first focuses on a change in political orientation. The second focuses on a change in political activism on the part of those who oppose reforms. The third focuses on trust in political actors. The fourth focuses on the economic situation. There is also an important set of explanations for the rejection of reforms that we do not consider in this paper.
Keywords: 330